VALIDASI METODE UJI KADMIUM DALAM AIR SUMUR SECARA SPEKTROFOTOMETRI SERAPAN ATOM - Ade Heri; Sutanto Sutanto (Universitas Pakuan, 2016)
This validation is refer to SNI 17025:2008 which detail linearity, precision, and accuracy that conducted 7 times. The detection limit is taken from making standard by using AAS graphic from PG type 990 and then the result used for analyzing of cadmium in well water. 2 liter of the sample (that take from one well in designated area) is aspired into AAS with 228,8 nm wave length. According to the result of this method, got the linearity with coefficient regretion value 0,9997, detection limit 0,0028 mg/L, precision of unspike sample with RSD value RSD 10,77 % and precision of spike sample with RSD 0,16 %, and recovery for accuracy value 86,44 % - 90,30 %. This method give the result the meet the requirement for validation applied, so that the method can be used for routine of cadmium content in well water.Average of cadmium content in well water is 0,0247 mg/L. Keyword : Validation methode, Cadmium, Well water, Atomic Absorption Spectrophotometer